Detrital zircons record the provenance and source-to-sink process in the northwestern margin of the South China Sea - Cui, Heqi; Wang, Ce; Su, Ming; Lei, Yaping; Zeng, Letian; Jia, Junmin (Frontiers in Marine Science, 2024)
The northwestern continental margin of the South China Sea, extending from the broad shelf and canyon-growth slope across the Xisha Trough, represents a relic crustal rift that eventually connects to the abyssal plain. However, the provenance and source-to-sink process of sediments in this special topography remains unclear. In this study, we present the detrital zircon U-Pb geochronology of surface sediments from the northwestern margin of the South China Sea to identify the sediment provenance, track the transport pathway, and understand the source-to-sink process in this margin. The results showed that detrital zircons exhibit a wide range of U-Pb ages from 3,062.9 to 41.5 Ma and are characterized by peaks centered on 140–154 Ma, 240–258 Ma, 425–452 Ma, and 738–991 Ma. Statistical analysis indicated that the clastic sediments on the shelf closely resemble those sourced from the Pearl River system. Conversely, sediments on the slope and abyssal plain demonstrated characteristics indicative of multiple sources, primarily originating from the Pearl River, with a minor contribution from the Red River. Further quantitative study revealed a progressive increase (from 8.2% to 43.2%) in the prevalence of Red River-derived sediments with ascending water depth on the shelf and slope, whereas sediment influx in the deepest sector remains predominantly sourced from the Pearl River. This study emphasizes the controls of topography and currents in modulating the transportation of coarse-grained and fine-grained sediments within the source-to-sink system and provides a favorable solution for reconstructing the sedimentary process in continental margins.